Bulletin - New Straits Times, (2008)
universiti Putra Malaysia's Faculty Of Medicine and Health Science and The Bioscience Institute are organising Kenanga Health Carnival 2008 today at Kampung Kenanga, Gombak from 7am to 6pm.